Neurologic interventions for physical therapy - Martin, Suzanne; Martin, Suzanne (Saunders an imprint of Elsevier Inc, 2016)
"Master the role of the physical therapist or physical therapist assistant in neurologic rehabilitation! Neurologic Interventions for Physical Therapy, 3rd Edition helps you develop skills in the treatment interventions needed to improve the function of patients with neurologic deficits. It provides a solid foundation in neuroanatomy, motor control, and motor development, and offers clear, how-to guidelines to rehabilitation procedures. Case studies help you follow best practices for the treatment of children and adults with neuromuscular impairments caused by events such as spinal cord injuries, cerebral palsy, and traumatic brain injuries. Written by physical therapy experts Suzanne 'Tink' Martin and Mary Kessler, this market-leading text will help you prepare for the neurological portion of the PTA certification exam and begin a successful career in physical therapy practice."--Publisher.